3- and 4-(α-diazobenzyl)pyridine-N-oxides as photoresponsive magnetic couplers for 2p–4f heterospin systems: formation of carbene–TbIII and carbene–DyIII single-molecule magnets. Issue 16 (22nd March 2016) - Murashima, Kensuke; Karasawa, Satoru; Yoza, Kenji; Inagaki, Yuji; Koga, Noboru
Abstract : Dinuclear Tb III – and Dy III –D1pyO complexes were photolyzed to afford heterospin SMMs with U eff / k B = 30 and 39 K, respectively. Abstract : 3- and 4-(α-diazophenyl)pyridine- N -oxides, 3- and4-D1pyO, were prepared as new photoresponsive magnetic couplers in heterospin systems. Lanthanide dinuclear complexes, [Ln III (tta)3 (4-D1pyO )]2 ; Ln III = Gd (1d ), Tb (2d ), and Dy (3d ) and tta = 4, 4, 4-trifluoro-1-(2-thienyl)-1, 3-butanedionate, bridged with4-D1pyO in μ2 coordination mode were obtained. The obtained1d, 2d, and3d were isostructures. The isomeric complex, [Tb III (tta)3 (3-D1pyO )]2 was also prepared. In the carbene-Ln III complexes [Ln III (tta)3 (4- and3-C1pyO )]2 generated by photolysis, C1pyO regioselectively interacted with the Ln III ions through pyridine- N -oxide, in which the magnetic coupling of4-C1pyO was weakly ferromagnetic, while that of3-C1pyO was insignificant. Before and after irradiation of1d, no SMM behavior was observed. In contrast, the Tb III and Dy III complexes being anisotropic functioned as heterospin SMMs. Before irradiation, 2d showed no SMM behavior. After irradiation, two species showing slow magnetic relaxations were produced and one of them exhibited SMM behavior with the thermal activation barrier, U eff / k B = 30 K, and τ 0 = 5.8 × 10 −8 s. In3d, SMM behaviors were observed before and after irradiation, and the U eff / k B value of 102 K ( τ 0 = 3.6 × 10 −7 s) before irradiation was reduced to 39 K ( τ 0 = 1.5 × 10 −8 s) after irradiation.